2014
DOI: 10.1177/1087054714529819
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD Screening in Alcohol-Dependent Patients Using the Wender–Utah Rating Scale and the Adult ADHD Self-Report Scale

Abstract: WURS and ASRS are useful tools in the diagnosis of adult ADHD in alcohol-dependent patients; with the use of both instruments, the psychometric properties are substantially improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
2
34
1
1
Order By: Relevance
“…Accepting a cut-off point of 14 on the ASRS-6, van de Glind et al (11) found a sensitivity of 84.95% and a specificity of 66.95%, Daigre et al (43) found a sensitivity of 86.7% and a specificity of 66.1%, and finally, in a sample of patients with AUD, Roncero et al (8) found a sensitivity of 83.3% and a specificity of 66.1%, PPV of 32.3%, and an NPV of 95.4%. In the present study, the cut-off score of 10 for ASRS-6 corresponded to sensitivity=0.75, specificity=0.79, PPV=0.46, and NPV=0.93.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accepting a cut-off point of 14 on the ASRS-6, van de Glind et al (11) found a sensitivity of 84.95% and a specificity of 66.95%, Daigre et al (43) found a sensitivity of 86.7% and a specificity of 66.1%, and finally, in a sample of patients with AUD, Roncero et al (8) found a sensitivity of 83.3% and a specificity of 66.1%, PPV of 32.3%, and an NPV of 95.4%. In the present study, the cut-off score of 10 for ASRS-6 corresponded to sensitivity=0.75, specificity=0.79, PPV=0.46, and NPV=0.93.…”
Section: Discussionmentioning
confidence: 99%
“…Its 6-item screening version has been shown to outperform the full 18-item version in sensitivity (68.7% vs. 56.3%) and specificity (99.5% vs. 98.3%) in the American general population (9,10). The ASRS-6 has also been reported to possess satisfactory psychometric properties in patients with addiction disorders (11,39,40,(42)(43)(44). Specifically, in samples of patients with AUD, psychometric characteristics have been analyzed by three studies, in which satisfactory properties have been found (8,11,43).…”
Section: Instruments For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been frequently used for community epidemiological research as it has strong concordance with clinical diagnoses, with a reported area under the curve (AUC) of 0.90. A major drawback with the brief ASRS is that it solely provides information on current symptoms, requiring researchers to administer a different measure for retrospective assessment (Daigre et al, 2015, Ginsberg et al, 2012, such as the Wender Utah Rating Scale (Ward et al, 1993). Furthermore, screening tools might differ in their predictive validity amongst different patient samples.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, screening tools might differ in their predictive validity amongst different patient samples. Alternative cut-off scores have been reported for the ASRS depending on the population, for example for screening ADHD among alcohol dependent patients (Daigre et al, 2015) and for substance dependent patients seeking-treatment (van Emmerik-van Oortmerssen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%